2011
DOI: 10.1534/genetics.110.124172
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Polymerase Activity ofSaccharomyces cerevisiaeRev1 is Biologically Significant

Abstract: A cell's ability to tolerate DNA damage is directly connected to the human development of diseases and cancer. To better understand the processes underlying mutagenesis, we studied the cell's reliance on the potentially error-prone translesion synthesis (TLS), and an error-free, template-switching pathway in Saccharomyces cerevisiae. The primary proteins mediating S. cerevisiae TLS are three DNA polymerases (Pols): Rev1, Pol z (Rev3/7), and Pol h (Rad30), all with human homologs. Rev1's noncatalytic role in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 71 publications
(111 reference statements)
3
45
0
2
Order By: Relevance
“…Role for REV1 in TLS-Among the TLS-specialized DNA polymerases, REV1 plays a unique role in TLS by serving as a protein platform (40) although its deoxycytidyl transferase activity plays a role for TLS past some lesions (10,11). It is generally thought that REV1 and pol function together during TLS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Role for REV1 in TLS-Among the TLS-specialized DNA polymerases, REV1 plays a unique role in TLS by serving as a protein platform (40) although its deoxycytidyl transferase activity plays a role for TLS past some lesions (10,11). It is generally thought that REV1 and pol function together during TLS.…”
Section: Discussionmentioning
confidence: 99%
“…REV1, another member of the Y family, does not have a canonical DNA polymerase activity but instead shows a deoxycytidyl transferase activity (8,9). This enzyme activity plays a role in TLS across certain classes of lesions (10,11). REV1 also plays a noncatalytic role in TLS (12) and physically interacts with the other Y family polymerases (13,14) and the REV7 subunit of pol (15,16).…”
mentioning
confidence: 99%
“…6). Indeed, it has been reported that the Rev1¢s noncatalytic role was biologically significant for UV resistance in yeast (Wiltrout & Walker 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Dbh belongs to the Y-family of translesion (TLS) DNA polymerases that can accurately bypass a variety of damaged DNA templates (Yang and Woodgate 2007). Members of the Y-family include Dpo4 from Sulfolobus solfataricus, pol IV [E. coli, (Wagner et al 1999)] mammalian pol j (Ogi et al 1999;Ohashi et al 2000;Gerlach et al 2001), pol g (Johnson et al 1999a, b), pol i (McDonald et al 1999;Tissier et al 2000), and Rev1 (Lin et al 1999;Wiltrout and Walker 2011). In particular, Dbh shares 54 % sequence identity to Dpo4.…”
Section: Biological Contextmentioning
confidence: 99%